PERAN KOMUNIKASI TERHADAP KESEHATAN MENTAL SPIRITUAL GENERASI Z DI ERA MODERN - Aspar, Aspar; Said, Nurhidayat Muhammad (Al-Mishbah: Jurnal Ilmu Dakwah dan Komunikasi, 2025)
This research aims to examine the role of communication on the spiritual mental health of generation Z in the modern era, focusing on the impact of social media on mental health, the utilisation of digital da'wah for spiritual awareness, and the application of Sufism in managing the influence of technology. This type of research is qualitative with a library research method to collect data from various library sources, such as books, journals, and scientific works related to the object of research. Good interpersonal communication provides important emotional support for Generation Z, supporting their mental well-being. While social media has its benefits, its negative impacts, such as information pollution and social pressure, need to be considered. Utilising digital platforms for da'wah and spiritual content can strengthen Generation Z's spiritual awareness. Approaches such as Sufism help them develop a healthy digital ethic, avoid technology dependency, and maintain a spiritual connection with God, although challenges such as misinformation and unrealistic expectations need to be managed wisely Abstrak Penelitian ini bertujuan mengkaji peran komunikasi terhadap kesehatan mental spiritual generasi Z di era modern, dengan fokus pada dampak media sosial terhadap kesehatan mental, pemanfaatan dakwah digital untuk kesadaran spiritual, serta penerapan tasawuf dalam mengelola pengaruh teknologi. Jenis penelitian ini adalah kualitatif dengan metode penelitian kepustakaan untuk mengumpulkan data dari berbagai sumber pustaka, seperti buku, jurnal, dan karya ilmiah terkait objek penelitian. Komunikasi interpersonal yang baik memberikan dukungan emosional penting bagi Generasi Z, mendukung kesejahteraan mental mereka. Meskipun media sosial memiliki manfaat, dampak negatifnya, seperti polusi informasi dan tekanan sosial, perlu diperhatikan. Pemanfaatan platform digital untuk dakwah dan konten spiritual dapat memperkuat kesadaran spiritual generasi Z. Pendekatan seperti tasawuf membantu mereka mengembangkan etika digital sehat, menghindari ketergantungan teknologi, dan menjaga hubungan spiritual dengan Tuhan, meski tantangan seperti informasi salah dan ekspektasi tak realistis perlu dikelola dengan bijak.